A bánsági német bevándorlás okai - Marjanucz, László (Közép-Európai Közlemények, 2010)
One of the most important questions of the Hungarian history in the 18. century was the filling of country with people. The sorrowful legacy of the 150 year-long Ottoman occupation was the depopulation of the parts of Hungary which were under Turkish rule. The Habsurgs settled organizedly the greatest number of colonists to Hungary from Germany in the 18. century. A lots of German colonists settled down in the „ Temescher Banat” Their folk idiom „ Svabian” became known to the public, although most of the settlers came from other lands of the Holy Roman Empire. Only 25% of colonists were Svabian by birth, the others came from Lothringen, Trier, Luxemburg, and from other lands of South-West Germany. Who they were, why did they leave their homeland? Up to the present lives the opinion, that the over population of that place caused the emigration to Hungary. It is a simplified answer to the problem. The local conditions were very complicated, from which the answer could be deduced. This situation can be explained by the conjunction of the decaying feudalism and the absence of the state centralization, which had a negative effect. The German serfs were unprotected from their landowner. The emigration appeared as a way out from the difficult social position. Many people found a new home in the Temescher Banat, and as a real pioneer they frequented the devastated territory by the Turks.